157k views
2 votes
−10x + 6(x − 5) = 12x − 62

User DasPete
by
4.8k points

2 Answers

5 votes

Answer: x=2

Explanation:

first you distribute -10x+6x-30=12x-62

then combine all like terms -16x=-32

then divide -16x/-16=-32/-16

answer x=2

User Theamoeba
by
5.3k points
1 vote

Answer:


x=2

Explanation:

So we have:


-10x+6(x-5)=12x-62

Distribute:


-10x+6x-30=12x-62

Combine like terms:


-4x-30=12x-62

Subtract 12x from both sides:


-16x-30=-62

Add 30 to both sides:


-16x=-32

Divide both sides by -16:


x=2

And that's our answer :)

User Fred Collins
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.